NEW STABILITY-INDICATING RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE DETERMINATION OF ROSUVASTATIN (CALCIUM) IN PHARMACEUTICAL DOSAGE FORMS (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
A stability indicating, accurate, specific, linear and sensitive reverse phase-HPLC method was developed and validated for the determination of Rosuvastatin calcium (ROS) in pharmaceutical dosage form. The chromatographic separation was performed using Eclipse XDB plus C18 Column (4.6 × 150 mm, 5μm particle size). Mobile phase was made by using Acetonitrile: Water (60:40 v/v) at a flow rate of 1.0 ml/min with the detection wavelength at 242 nm. The retention time of ROS was found to be about 1.787 min. The linearity was obtained in the concentration range of 10-50 μg/ml with a correlation coefficient of 0.999. The percentage purity of ROS was found to be 100.06 %. The percentage recovery was determined for ROS and found to be 100.53 %. The developed analytical method was validated for linearity, precision, accuracy, ruggedness, robustness, specificity and system suitability which were within the acceptance limit according to ICH guidelines. All the degradation products obtained by stress conditions were found to be well separated from the principal peak, which means that the ROS peaks were highly pure in all chromatograms obtained. The developed method was found to be applicable for routine quality control and stability analysis of ROS in pharmaceutical dosage forms.